Systematic exploration of sustainability in higher education: a tertiary perspective - Aghajani, M.; Memari, A.; Tumpa, R.J.; Ruge, Gesa (2024)
Purpose: This study aims to systematically examine 69 secondary studies to understand trends and implications in sustainability in higher education (SHE), addressing gaps in secondary studies, which often lack comprehensive thematic overviews that hinder future directions. Design/methodology/approach: This tertiary study uses meticulous thematic coding to unveil overarching themes and future research directions across seven SHE areas: institutional frameworks, campus operations, education, research, outreach and collaborations, campus experiences and assessment and reporting. Findings: The analysis reveals challenges higher education institutions (HEIs) face in integrating sustainability, highlighting the need for a holistic approach. Barriers such as awareness deficits and resistance to change emphasize the importance of interdisciplinary research. Emphasizing holistic integration and innovation is vital for seamlessly embedding sustainability within HEIs. Practical implications: Key future research themes include holistic approaches to sustainability integration, leadership for sustainable change and innovative pedagogical approaches. Additionally, it is important to explore transdisciplinary approaches in sustainability research and the role of research centers and funding in addressing sustainability challenges. Originality/value: This study provides a comprehensive overview of SHE, offering insights for researchers and practitioners, and serves as a resource for advancing sustainable educational practices.